Kiai’s Transformational Leadership-Based Supervision Model for Improving Santri’s Multidimensional Learning Outcomes - Muhammad Fathan Rusyadi (Lembaga Peneltian Universitas Islam Internasional Darullughah Wadda'wah, 2026)
Supervision in Islamic boarding schools (pesantren) is often viewed merely as an administrative function, neglecting its holistic impact on students’ learning outcomes. This study aims to analyze the effectiveness of Kiai’s transformational leadership-based supervision in improving santri’s learning outcomes at Pondok Pesantren Raudhatut Thalibin Amuntai. Utilizing a qualitative approach with a descriptive case study design, data were collected through in-depth interviews, observations, and documentation involving the Kiai, teachers, dorm wardens, and students. Data analysis followed the interactive model of Miles, Huberman, and Saldaña. The results indicate that Mu’allim KH. Ahmad Mu’thi implements holistic supervision that integrates physical monitoring and CCTV technology with a persuasive-dialogic approach. This practice reflects four dimensions of transformational leadership: idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. The impact is evident in the improvement of students’ multidimensional learning outcomes, including enhanced academic discipline, higher exam performance, values-based moral internalization, and the establishment of a continuous learning culture. In conclusion, the Kiai’s transformational supervision model successfully blends modern managerial-technological governance with traditional spiritual-charismatic authority to improve the quality of Islamic education.